Novel compound variants of the AR and MAP3K1 genes are related to the clinical heterogeneity of androgen insensitivity syndrome. Issue 5 (7th May 2020) - Cheng, Yiping; Sun, Yan; Ji, Yiming; Jiang, Dongqing; Teng, Guoxin; Zhou, Xiaoming; Zhou, Xinli; Li, Guimei; Xu, Chao
Abstract: Androgen insensitivity syndrome (AIS; OMIM 300068) is the most frequent cause of 46, XY disorders of sex development (DSD). However, the correlation between genotype and phenotype has not been determined. We conducted a systematic analysis of the clinical characteristics, hormone levels, ultrasonography data and histopathology of a 46, XY Chinese patient with AIS. The family was followed up for nearly 8 years. We applied whole-exome sequencing (WES) for genetic analysis of the pedigree and performed bioinformatic analysis of the identified variants. Human embryonic kidney 293T/17 (HEK293T/17) cells were transiently transfected with wild-type or mutant AR and MAP3K1 plasmid. Cell lysates were used to analyze androgen receptor (AR) production. A novel hemizygous AR variant (c.2070C>A, p. His690Glu) and a rare heterozygous MAP3K1 variant (c.778C>T, p. Arg260Cys) were identified by WES in the proband and her mother. Bioinformatic analysis predicted these two variants to be pathogenic. Multiple amino acid sequence alignments showed that p. His690 and p. Arg260 are conserved among various species. His690Glu is a mutation that decreased the AR production, whereas the Arg260Cys mutation increased the AR production. The novel compound variants of the AR and MAP3K1 genes also increased the production of AR protein. Thus, the phenotype of the patient may be caused by defects in both the AR and MAP3K1 signaling pathways. Compound variants of the AR and MAP3K1 genes resulted in a specific phenotype in this patient with AIS. WES might reveal genetic variants that explain the heterogeneity of AIS.